THE SYSTEM OF JOINT RESPONSIBILITY IN ASSAKINAH COOPERATIVE AS THE IMPLEMENTATION OF TA'AWUN - Ainaul Mardliyyah; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2020)
This research aims to determine how the application of ta'awun in the joint responsibility system in the Assakinah cooperative. The method used in this research is a qualitative approach with a case study method. The object of this research is the Assakinah cooperative in Sidoarjo. Data was collected by interviewing five informants, namely, head of the cooperative, the secretary, treasurer, group assistant and group leader. The results of this research indicate that the implementation of the joint responsibility system that exists in Assakinah cooperatives is in accordance with two Islamic teachings, namely, musyawarah or mufakat and mutual cooperation. However, the joint responsibility system that exists in Assakinah cooperatives is not yet fully joint responsibility. This is because in practice, members that are unable to pay their debts, not always getting help from the group.Keywords: Ta’awun, sharia cooperative, Joint Liability, joint responsibility.REFFERENCE Ajija, Shochrul Rohmatul, dkk. (2018). Koperasi BMT teori, aplikasi dan inovasi. Karanganyar: CV Inti Media Komunika.Buchori, Nur S. (2012). Koperasi syari’ah teori dan praktik. Banten: Pustaka Aufa Media.Ismail, Iriani. (2011). Koperasi dan usaha mikro kecil menengah. Malang: Lembaga Penerbitan Fakultas Pertanian Universitas Brawijaya Jatman, Darmanto. dkk. (2001). Bunga rampai tanggung renteng. Malang: Limpad.K. Yin, Robert. (2011). Studi kasus: Desain dan metode. Jakarta: PT. RajaGrafindo Persada.K. Yin, Robert. (2015). Studi kasus: Desain dan metode. Jakarta: PT. RajaGrafindo Persada.Qomaro, Galuh Widitya dan Oktasari, Armyza. (2018). Manisfestasi konsep ta'awun dalam zaakwaarneming perspektif hukum perikatan. Jurnal Et-Tijarie, 5(1), 11-25.